MENINGKATKAN KEMAMPUAN MEMBACA MELALUI PERMAINAN KOMPUTER PADA SISWA KELAS I DI SDN KALIBATA 03 PAGI JAKARTA TIMUR - Yarmi, Gusty -; Widyastuti, Resty - (Universitas Muhammadiyah Surakarta, 2014)
In general, this study aims to improve the reading skills of students in grade 1 SDNKalibata 03 Pagimelalui learning to apply computer games. The results of the analysisof the data shows computer games can improve students’ reading class I, especiallyreading the sentence correctly, read the sentence without eliminating one of the words inthe sentence, read the sentence without adding a word, read the sentences with the rightintonation, read by observing a pause (for stop, breathe), read with the firm, loud volume,the volume of the sound heard is stable in the first grade students of SDN 03 PagiKalibata. It is characterized by an increase in the value of reading skills of students ineach cycle